IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) J99 FOUNDATION DALAM UPAYA MENINGKATKAN CITRA PERUSAHAAN MELALUI SEKTOR SOSIAL BUDAYA DI KAWASAN MALANG RAYA - Roziqin, Akhmad Ainur; Winata, Muhammad Danu (The Commercium, 2024)
Company image is one form of perception of a problem which includes visual impressions to observations. There are so many improvement processes based on products, behaviors, and services that are directly faced with the community and become core values formulated by the company. The classification of the existence of CSR programs in the cultural sector in the J99 foundation is certainly the main object in carrying out CSR implementation in the greater Malang area. The implementation process conveyed is not only accepted by the public, but also able to become a reputation capital to achievements that aim to create harmony between others. The method used in this study certainly has a correlation with the number of programs in the socio-cultural sector that are equipped with facts and reality. The results of this study can be concluded that there is a sustainability program that has a positive impact both in terms of social, economic, and also the environment. In addition, there is also an increase in awareness in responding to social life.